PENGARUH PENGAWASAN KEUANGAN DAN PENYAJIAN LAPORAN KEUANGAN TERHADAP KINERJA PEMERINTAH BERKONSEP VALUE FOR MONEY PADA PEMERINTAH KOTA MALANG - Elda, Natalia; Sulistyo, Sulistyo; Dianawati, Eris (Jurnal Riset Mahasiswa Akuntansi, 2020)
This study aims to examine and explain the effect of Financial Supervision and Presentation of Financial Statements on Government Performance Conceptual Value for Money in Malang. The data analysis model used is multiple linear regression. Sampling is done by purposive sampling method, which is sampling based on certain criteria to be used as respondents in this study. Data collection in this study used a questionnaire that was distributed to employees of the Regional Financial and Asset Management Agency, amounting to 46 questionnaires or (92%). Classical assumption testing includes multicollinearity test, heteroscedasticity test, autocorrelation test and normality test. Hypothesis testing using the F test and t test. Based on the results of data analysis research with the help of SPSS 16.00 shows that 1) There is a significant influence between Financial Supervision and Presentation of Financial Statements on Government Performance Concepts Value for Money. 2) There is a positive and significant influence between Financial Supervision on the Performance of the Government concept of Value For Money. 3) There is a positive and significant effect between the Presentation of Financial Statements on the government's performance concept of value for money.